[OA187] Transfer of minibeam radiation therapy into a cost-effective equipment: A proof of concept. (August 2018) - Prezado, Yolanda; Santos, Morgane Dos; Gonzalez, Wilfredo; Jouvion, Gregory; Guardiola, Consuelo; Heinrich, Sophie; Labiod, dalila; Juchaux, Marjorie; Jourdain, Laurene; Sebrié, Catherine; Pouzoulet, Frederic
Abstract : Introduction: Minibeam radiation therapy (MBRT) is an innovative synchrotron radiotherapy technique able to shift the normal tissue complication probability curves to very high doses[1] . MBRT seem to involve different biological mechanisms (not well understood yet) different from those in standard RT. However, its exploration was hindered due to the limited and expensive beamtime at synchrotrons. The aim of this work was to evaluate the feasibility of the implementation of MBRT into cost-effective equipment. Materials and methods: A series of modifications of a small animal irradiator were performed to make it suitable for MBRT experiments. In particular, an adapted collimator was designed by means of Monte Carlo simulations (Geant4). Peak to valley dose ratio values and full width half at maximum similar to those obtained at the European synchrotron radiation facility (ESRF)[2] were used as figure of merit. As a proof of concept, the whole brain of two groups were irradiated: a first group received conventional (broad beam) irradiations, the second series was irradiated with MBRT. The same average dose was deposited in both cases, 20 ± 1 Gy, which corresponds to 58 Gy peak dose in the MBRT case. The animals were followed-up for 6.5 months. At the end of the study a magnetic resonance imaging (MRI) evaluation and histological analysis were performed. Results: The dosimetric features of our system were shown to be similar to the synchrotron ones[2] . Concerning the in vivo experiment, rats treated with conventional irradiation exhibited very important brain damage, including radionecrosis. In contrast, no substantial brain damage was observed in the animals of the MBRT group. Conclusions: This work proves the feasibility of the transfer of MBRT outside synchrotron sources towards a small animal irradiator[3] . This is the first time that such an evaluation is done with millimetre-sized minibeams in the brain, which opens the door for future implementations with less technically demanding and very compact systems.